Sensitization of renal carcinoma cells to TRAIL-induced apoptosis by rocaglamide and analogs. Issue 1 (December 2018) - Nalli, Ancy; Brown, Lauren; Thomas, Cheryl; Sayers, Thomas; Porco, John; Henrich, Curtis
Abstract Rocaglamide has been reported to sensitize several cell types to TRAIL-induced apoptosis. In recent years, advances in synthetic techniques have led to generation of novel rocaglamide analogs. However, these have not been extensively analyzed as TRAIL sensitizers, particularly in TRAIL-resistant renal cell carcinoma cells. Evaluation of rocaglamide and analogs identified 29 compounds that are able to sensitize TRAIL-resistant ACHN cells to TRAIL-induced, caspase-dependent apoptosis with sub-µM potency which correlated with their potency as protein synthesis inhibitors and with loss of cFLIP protein in the same cells. Rocaglamide alone induced cell cycle arrest, but not apoptosis. Rocaglates averaged 4–5-fold higher potency as TRAIL sensitizers than as protein synthesis inhibitors suggesting a potential window for maximizing TRAIL sensitization while minimizing effects of general protein synthesis inhibition. A wide range of other rocaglate effects (e .g . on JNK or RAF-MEK-ERK signaling, death receptor levels, ROS, ER stress, eIF4E phosphorylation) were assessed, but did not contribute to TRAIL sensitization. Other than a rapid loss of MCL-1, rocaglates had minimal effects on mitochondrial apoptotic pathway proteins. The identification of structurally diverse/mechanistically similar TRAIL sensitizing rocaglates provides insights into both rocaglate structure and function and potential further development for use in RCC-directed combination therapy.